Fabrication and Characterization of Silicon and Polysilicon Nanogaps Electrodes Using Size Reduction Technique for Chemical and Biomolecules Detection - Dhahi, Thakra S. (Institute of Nano Electronic Engineering, 2012)
The aim of this research work is to design, fabricate, characterize, and test nanogap-electrode based device for biochemical detection and DNA immobilization and hybridization detection. However, the focus of this research is to investigate electrically and chemically the effect of different materials and gap sizes on the nanogap electrodes design.